Relationship Between the Material Properties and Pyroelectric‐Generating Performance of PZTs. (7th February 2017) - Yamanaka, Satoru; Kim, Juyoung; Nakajima, Akira; Katou, Takanori; Kim, Yoonho; Fukuda, Tatsuo; Yoshii, Kenji; Nishihata, Yasuo; Baba, Masaaki; Yamada, Noboru; Nakayama, Tadachika; Takeda, Masatoshi; et al.
Abstract : In pyroelectric applications, the general figures of merit (FOMs) have been applied and reported near room temperature. We derived the modified FOMs in considering our electro‐thermodynamic cycle for the usage environment of automotive applications. The relationship between the material properties and generating performance of PZTs was investigated at various temperatures. The F D ¯ was suggested from FD, a FOM for a pyroelectric sensor, based on the modified pyroelectric coefficient (p); p ¯ . p ¯ was calculated by the change of the spontaneous polarization (PS ) according to a given temperature variation during one cycle;Δ PS /Δ T (Tmax −Tmin ). It was indicated that the F D ¯ could be effective as a FOM for the pyroelectric generating performance and the dielectric loss (tanδ ) significantly affected the generating performance in addition to p ¯ under high‐temperature and electric field conditions. Furthermore, of the PZTs tested, C‐91 sample which showed the highest generating performance resulted in a generating energy of 1.3 mW cm –3 in the engine dynamometer assessment. This is 13 times greater than the generating energy reported in a previous study of C‐6 (0.1 mW cm –3 ). Abstract : How can exhaust heat from automobiles be converted to renewable energy? To investigate this question, an innovative electro‐thermodynamic system is presented, based on the pyroelectric effect. The relationship between the material properties and generating performance is investigated utilizing a modified figure of merit. A generated energy of 1.3 mW cm −3 can be obtained, which is much higher than any previously obtained.